Systemic sepsis post arterial catheterism.: Tratamiento mediante remoción del foco y puente por el agujero obturador - Mazza, Milton; Bagnulo, Homero; Portos, Ruben; Rudnitsky, Omar (Cirugía del Uruguay, 1984)
Presented is a case of systemic sepsis arising from a ·teritis subsidiary to diagnostic arterial ca!heterism. Aulhor points out the case is an extremely rare occurrence and discusses surgical treatment of same.